Taxonomy of the leaf beetle genus Exomis Weise (Coleoptera: Chrysomelidae: Clytrini) with description of six new species from China - Wang, Feng-Yan; Zhou, Hong-Zhang (Zootaxa, 2020)
This publication revises the taxonomy of the leaf beetle genus Exomis Weise, 1889 (Coleoptera: Chrysomelidae: Clytrini) which is endemic to China. Six new species are described: E. deqinensis sp. nov., E. huangi sp. nov., E. pubescens sp. nov., E. pubipennis sp. nov., E. tanae sp. nov. and E. viridis sp. nov., in addition to two known species, namely E. degenevei Pic, 1932 and E. peplopteroides Weise, 1889. Exomis oblongum (Lopatin & Konstantinov, 2009) from China (Yunnan) is transferred to this genus as new combination. The total Chinese fauna of Exomis is thus increased to nine species. A key to these species is provided and, for each of them, also a color photo of habitus and line drawings of the aedeagus, spermatheca and kotpresse, in order to ease identification in the future.